Sex Differences in Recreational Fear: An Evolutionary Account of Media Preferences - Johannesen, Ida (Leviathan: Interdisciplinary Journal in English, 2024)
In this article I examine sex differences related to recreational fear, including theory on the evolved fear system, morbid curiosity, and disgust sensitivity. I use an evolutionary framework to argue that recreational fear can appeal specifically to women, with a focus on media preferences. Through an analysis of the true crime podcast My Favorite Murder and the slasher movie Halloween, I argue that both examples are popular with women, because they provide recreational fear in a way that aligns with women’s fears, curiosity, and threshold for disgust. They are relatively less scary than many other forms of frightening media. They also center around the fear of hostile conspecifics, which is common for women to experience. Because of this, they appeal to women’s morbid curiosity towards dangerous people and their motives. Lastly, they are careful to avoid excessive disgusting stimuli that could discourage a female audience from engaging.